KARAKTERISTIK MAKANAN TRADISIONAL BENGKULU BOLU SOM DENGAN VARIASI TEPUNG KELOR - Andwini Prasetya; Satria Wijaya; Methatias Ayu M (Jurnal Agroindustri Pangan, 2026)
Bolu som is a traditional Bengkulu cake shaped like a long rectangle with varying sizes, layered with pineapple jam inside, and then covered again with cake on top. Bolu som is always served at community events in the city of Bengkulu. This type of cake is moist, and the main ingredient used in making bolu som is usually wheat flour. This research aims to determine the effect of using moringa flour on the physical, chemical, and organoleptic characteristics of Bolu Som, in addition to analyzing revenue and profit, as well as identifying the best treatment in the processing of Bolu Som. This study involves six treatments, each wit a different composition ratio of raw materials, specifically wheat flour to moringa leaf powder: (100:0), (85:15), (70:30), (55:45), (40:60), and (25:75). The analyses conducted include physical analysis (texture and yield), organoleptic tests (taste, aroma, and color), selection of the best treatment, chemical analysis (moisture content, fat content, carbohydrate content, protein content, and antioxidant content), along with revenue and profit analysis of Bolu Som. The research results show the yield of various moringa flour to be 59.57% to 66.4%, with a texture of 2.24 mm to 3.84 mm. The organoleptic test on the taste, aroma, and color of the som cake showed an average taste value ranging from 1.96 (dislike) to 3.88 (like very much), an aroma ranging from 2.04 (dislike) to 3.92 (like very much), and a color ranging from 2.20 (dislike) to 3.96 (like very much). For the best treatment results, the combination of 85% wheat flour and 15% moringa flour was obtained. The results of the chemical analysis with the best treatment showed a moisture content of 28.10%, fat content of 11.35%, carbohydrate content of 19.23%, protein content of 11,672.92 mg/L, and antioxidant content of 236.21 mg/L.